Globalization and media : global village of Babel - Lule, Jack, 1954- (Lanham : Rowman & Littlefield, 2021)
"The fully updated fourth edition of this lively and accessible book argues for the central role of media in understanding and shaping globalization. By breaking down the economic, cultural, and political impact of media, and through a rich set of case studies, Jack Lule describes a divided global village, its destiny shaped by strife"--
Keywords: Globalization